Ultrastructural changes of platelet granules in patients with type 2 diabetes mellitus and hypertension in applying of angiotensin II receptor antagonists. - Pertseva, N. O. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Disorders of hemostasis in patients with arterial hypertension and diabetes mellitus type 2 are complex: growing aggregative activity of platelets and red blood cells, activation and degranulation of platelet antiaggregatory potential endothelium; reduced anticoagulant and fibrinolytic activity of blood. Objective. Quantification of ultrastructural changes in different types of platelet granules in patients with hypertension with high cardiovascular risk influenced the treatment losartan potassium. Methods. Ultrastructural studies of platelet granules was performed in 5 patients with hypertension 2nd degree (first clinical group), 10 patients with hypertension (second group) of degree 2 with type 2 diabetes in the stage subcompensation and 5 volunteers – healthy individuals (control group). To correct blood pressure was used angiotensin II receptor antagonist losartan (Lozap®, Zentiva). Ultrastructural analysis was performed at baseline and at 3, 6, 9 and 12 months of treatment. Results. For a detailed analysis of the process of activation and degranulation of platelets using transmission electron microscopy was carried out differential counting packing density of alpha and delta granules consisting hranulomera and numerical density lambda granules. In patients with hypertension platelet aggregation capacity was the most sensitive element of damage platelet hemostasis, which could largely normalized since 6-month use of losartan potassium. In the group of patients with hypertension and diabetes mellitus type 2, in which the initial contents dehranulated platelets was sharply increased, there was a significant positive trend for treatment involving losartan, which indicates its significant contribution to achieving normalization of dehranulated forms. Conclusion. Treatment with losartan potassium leads to a significant recovery of alpha-granules, normalize the content of dense bodyes and limitations of lysosomal activity in all groups.